2012
DOI: 10.1007/s15010-012-0302-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in antibiotic prescriptions: is area deprivation an explanation? Analysis of 1.2 million children in Germany

Abstract: Including area deprivation measures helped identify an influence of especially regional income and occupational deprivation on antibiotic prescriptions for children. Regional analysis such as this can help identify specific regions and groups of persons to address information programs on the risks of preventable antibiotic consumption and alternative treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 31 publications
3
48
0
8
Order By: Relevance
“…income, employment, education, municipal or district revenue, social capital, environment, security). The GIMD already showed significant associations with T2DM, reported in a previous study confined to five regional surveys [6], and with other health-related outcomes [33], [34]. For the present study, we calculated the GIMD scores for all urban and rural districts covering the whole of Germany.…”
Section: Methodsmentioning
confidence: 95%
“…income, employment, education, municipal or district revenue, social capital, environment, security). The GIMD already showed significant associations with T2DM, reported in a previous study confined to five regional surveys [6], and with other health-related outcomes [33], [34]. For the present study, we calculated the GIMD scores for all urban and rural districts covering the whole of Germany.…”
Section: Methodsmentioning
confidence: 95%
“…Regional disparities in prescription patterns based on insurance data have been described earlier for the prescription prevalence of antibiotic use. A recent German study showed a regional variation of 19–53% of antibiotic use in children which was partly explained by regional deprivation (especially by regional income and occupational deprivation) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Volumes vary more than threefold across countries, with Chile, Estonia and the Netherlands reporting the lowest volumes and Greece, Luxembourg and Belgium reporting volumes around 1.5 times the OECD average. Variation is likely to be explained, on the supply side, by differences in the regulation, guidelines and incentives that govern primary care prescribers and, on the demand side, by cultural differences in attitudes and expectations regarding the natural history and optimal treatment of infective illness (Akkerman et al, 2005;Koller et al, 2013). 2 shows the volume of quinolones and cephalosporins as a proportion of all antibiotics prescribed in primary care.…”
Section: Prescribing In Primary Carementioning
confidence: 99%